2021
DOI: 10.1002/advs.202101188
|View full text |Cite
|
Sign up to set email alerts
|

Survival‐Assured Liver Injury Preconditioning (SALIC) Enables Robust Expansion of Human Hepatocytes in Fah–/–Rag2–/–IL2rg–/– Rats

Abstract: Although liver-humanized animals are desirable tools for drug development and expansion of human hepatocytes in large quantities, their development is restricted to mice. In animals larger than mice, a precondition for efficient liver humanization remains preliminary because of different xeno-repopulation kinetics in livers of larger sizes. Since rats are ten times larger than mice and widely used in pharmacological studies, liver-humanized rats are more preferable. Here, Fah -/-Rag2 -/-IL2rg -/-(FRG) rats are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The success of the FRG humanized liver mouse model has led to demand for an equivalent recipient rat model. However, despite the successful generation of Fah null and Rag2 null, and Il2rg null rats by different groups more than 5 years ago 10,13,16 , bringing all 3 alleles together in rats through crossing is time consuming and logistically challenging, and the first FRG rat model was just published recently 9 . In this report, we sequentially introduced www.nature.com/scientificreports/ additional mutations through gene targeting in one-cell-stage embryos of animals carrying the homozygous alleles already modified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The success of the FRG humanized liver mouse model has led to demand for an equivalent recipient rat model. However, despite the successful generation of Fah null and Rag2 null, and Il2rg null rats by different groups more than 5 years ago 10,13,16 , bringing all 3 alleles together in rats through crossing is time consuming and logistically challenging, and the first FRG rat model was just published recently 9 . In this report, we sequentially introduced www.nature.com/scientificreports/ additional mutations through gene targeting in one-cell-stage embryos of animals carrying the homozygous alleles already modified.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 9 described a similar model of humanized rat livers, with several potentially relevant technical differences. First, although NTBC on-and-off cycling (albeit with slightly different schedule) was applied after implantation in both the current study and the other FRG rat humanized liver model described by Zhang et al 9 , we pre-conditioned recipient rats through dosing with adenovirus encoding urokinase-plasminogen activator (uPA) 24 hours before hepatocyte implantation, rather than treating with retrosine 2 weeks before cell transplantation followed by gradual NTBC withdrawal. In addition, the approaches to genetically alter the rat ES cells were somewhat different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humanized liver mouse and rat models, in which donor human hepatocytes repopulate recipient rodent livers, have been widely used to study human liver biology, diseases, and therapeutics (1)(2)(3)(4)(5)(6). However, it has been widely observed that engrafted human hepatocytes in both humanized liver mice and rats show defects, including increased lipid droplet accumulation (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%